Toward Just Participation: Dynamics Of Empowerment Communication In Tourism-Village Dvelopment - Yuli Setyowati; Fadjarini Sulistyowati; Habib Muhsin (Profetik: Jurnal Komunikasi, 2025)
Sustainable tourism development requires community participation as local involvement contributes to community welfare as is the case in Sambirejo Village  Tebing Breksi (Breksi Cliff) tourism. The study aims to: 1) explore and interpret the dynamics of empowerment communication in the development of the Sambirejo tourism village seen from the aspects of participation, utilization of community potential, and empowerment communication efforts that have been carried out; 2) the dynamics of empowerment communication from the perspective of sustainable tourism. This research employs a descriptive qualitative research design, with data collected through observation, interviews, focus group discussions (FGDs), and documentation. Informants were selected purposely, consisting of Village Heads, Village Secretaries, BUMDes (Village Owned Enterprises) managers, tourism actors, and community members. The results indicate that community participation in Sambirejo Village is quite high, but this involvement is not fair and equitable. Further efforts are needed to encourage broader  and more inclusive participation Community Empowerment is carried out based on the principles of community-based tourism namely empowerment in economic, social, political, cultural, and environmental aspects